POSTAWY MŁODZIEŻY AKADEMICKIEJ MIASTA POZNANIA WOBEC INSTYTUCJI MAŁŻEŃSTWA - Ignatczyk, Walentyna (Wydział Prawa i Administracji UAM, 2005)
The results of a survey conducted among Poznan students in the years 2002-2003 carried out to determine their preferences when it comes to the choice: career or family life, their attitudes to the institution of marriage, their preferred age to get married and the hierarchy of family values are presented. The results of the survey confirm the hypothesis that the institution of marriage still prevails. As many as 89.6 of the respondents indicated an intention to get married; they also placed family before career. At the same time, however, the young people are very sensitive to economic difficulties - 84% said that economic hardships might modify the attitudes they expressed in the survey. Consequently, it is expected that the number of informal, long-term or short-term relations between young people will be growing, especially since most students show a liberal attitude in that respect. The results o f the recent survey as well as those of the one carried out a few years earlier confirm that the changing attitudes to marriage among young people are being shaped by the economic factor. To stop or change that, adequate social policy and the state’s pro-family policy will be necessary.
ATTITUDES TO THE INSTITUTION OF MARRIAGE AMONG THE STUDENT COMMUNITY IN POZNAN